2017
DOI: 10.1186/s12943-017-0742-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in cancer metastasis: a better understanding to “seed and soil” hypothesis

Abstract: Metastasis has intrigued researchers for more than 100 years. Despite the development of technologies and therapeutic strategies, metastasis is still the major cause of cancer-related death until today. The famous “seed and soil” hypothesis is widely cited and accepted, and it still provides significant instructions in cancer research until today. To our knowledge, there are few reviews that comprehensively and correlatively focus on both the seed and soil factors involved in cancer metastasis; moreover, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(199 citation statements)
references
References 195 publications
(263 reference statements)
5
191
0
3
Order By: Relevance
“…39 Ensuing hypoxia and redox status alterations are considered as key components of the premetastatic remodelling of target organs. 40 An increase in the oxidative stress marker 2-OH-E + was observed in premetastatic tissues. 41 The expression of NFE2L2 was decreased in hepatocellular carcinoma and increased in alcoholic cirrhosis and end-stage liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Ensuing hypoxia and redox status alterations are considered as key components of the premetastatic remodelling of target organs. 40 An increase in the oxidative stress marker 2-OH-E + was observed in premetastatic tissues. 41 The expression of NFE2L2 was decreased in hepatocellular carcinoma and increased in alcoholic cirrhosis and end-stage liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The molecule NFE2L2 modulates antioxidant response and maintains cell redox homeostasis, controlling the expression of genes involved in the elimination of oxidants and electrophilic agents . Ensuing hypoxia and redox status alterations are considered as key components of the premetastatic remodelling of target organs . An increase in the oxidative stress marker 2‐OH‐E + was observed in premetastatic tissues .…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of "seed and soil" denotes that metastatic tumor cells could form secondary tumors only in permissive tissues with organ-specific soils (30). In other words, organ-specific metastasis may not only depend on the intrinsic abilities of cancer cells to cross biologic barriers, but also on metastatic microenvironments at distant organ, such as the microvascular system.…”
Section: Discussionmentioning
confidence: 99%
“…A major role in the metastatic cascade plays the phenomenon of epithelial to mesenchymal transition (EMT) whereby epithelial cells lose their epithelial features and acquire mesenchymal cells traits which allow them to invade adjacent tissues and display migratory properties. The metastatic cascade is a multistep complex process and can be divided in the following phases: (1) invasion of the extracellular matrix (ECM) and degradation of ECM proteins through the activity of matrix metalloproteinases (MMPs), (2) intravasation, (3) resistance to anoikis and survival in the peripheral blood, (4) extravasation, and (5) seeding of a distant body site by clones of neoplastic cells with high metastatic potential [192,200,201]. A number of studies have shown the involvement of lncRNAs in the metastatic progression of osteosarcoma through modulation of metalloproteinase expression, especially MMP-2 and MMP-9 [202,203].…”
Section: Lncrnas and Invasion/metastasis In Osteosarcomamentioning
confidence: 99%